Hall effect on magnetic reconnection at the Earth's magnetopause - Morales, Laura Fernanda (2005)
We analyze in situ observations of magnetic reconnection at the Earth magnetopause to estimate the importance of the Hall current during the merging of interplanetary and magnetospheric magnetic field lines. The reconnection process is studied through numerical simulations, integrating the Hall MHD equations in 2.5 dimensions. A large influence of the Hall effect is found, which can be measured by a significant increase of the reconnection rate.